Essential skills in call class: enhancing searching and language skills - Hassan, Haslina; Mohin, Mohaida (IIUM Press and IPPTN, 2009)
Introduction: In the quest of making learning more relevant in the contemporary era of information and communication technology, the Internet is considered a valuable resource to both language teachers and learners (Singhal, 1997). With the World Wide Web (WWW), learners of many languages have access to an unprecedented amount of authentic target language information (Warschauer, 1998; Chun and Plass, 2000). The Internet offers a great deal of supplemental language activities for the teachers to select from and later these activities provide the students with additional practices in a specific area of language learning (Chafe, 1999). The content of the Internet is generally very current and the language used to present it is real and authentic (Brown, 1999). Moreover, the use of the Internet should be endorsed as a tool to be incorporated into classroom activity as it stimulates active learning where the students' language skills and their language learning experience would be enhanced (Wetzel and Chisholm, 1998). The activities can be equally enjoyed by both advanced and slow learners.